EFFECT OF MENTHOL ON THE TRANSDERMAL PERMEATION OF ACECLOFENAC FROM MICROEMULSION FORMULATION - Ahmed, Abdul Baquee; Das, Gouranga (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of this investigation was to enhance the transdermal permeation of aceclofenac (ACF) from microemulsion formulation using menthol as a natural permeation enhancer. Methods: Microemulsion containing 2% w/v of ACF was prepared by a titration method with different concentration of oil, surfactant and co-surfactant. The prepared microemulsion was evaluated for droplet size, viscosity, pH and in vitro skin permeation studies. Menthol at 3-8% w/w was added to the selected microemulsion formulation and their effect on skin permeation was evaluated across rat epidermis using modified Keshary-Chien diffusion cell. The Fourier transform infrared spectroscopy (FT-IR) was performed to understand the regulation action of menthol in the skin permeability barrier. Results: The average droplet size of the microemulsion was found to be 89.4±2.12 to 175.2±3.10 nm. The transdermal flux of the microemulsion containing 8% w/w menthol showed 2.9 fold increases in transdermal flux of ACF compared with the formulation without menthol. Result of FT-IR studies showed decrease in peak height of the symmetric and asymmetric C-H stretching vibrations may be because of the extraction of the stratum corneum (SC) lipids and the alteration of the skin permeability barrier. Conclusion: This result suggests that menthol significantly enhanced the transdermal permeation of ACF and may be an effective natural penetration enhancer for transdermal delivery of the drug.